PEMILIHAN SUPPLIER MINYAK JELANTAH BAHAN BAKU BIOSOLAR DENGAN METODE ELECTRE - Anatasya, Dita Riyantiin; Andriyanto, Teguh; Firliana, Rina; Sucipto, Sucipto (Universitas Islam Balitar Blitar, 2023)
CV. Fred Jelantah is a CV engaged in the industrial sector, namely suppliers of used cooking oil as raw material for biodiesel. In the process of meeting the needs for supply of goods, CV.Fred Jelantah requires more than one supplier. So far, CV. Fred Jelantah still uses a subjective process in considering supplier selection. This causes inaccuracies in the supply of goods such as oil quality and timeliness of supply. The research objective of modeling a decision support system using the ELECTRE method is to be able to provide the best supplier references accurately and subjectively unconventionally for CV. Fred Jelantah. In calculating the ELECTRE method, 4 alternatives and 5 criteria are determined. Based on the results of the research conducted, the highest ranking results were obtained, namely the Jelantah Kelud and Kuli Jelantah alternatives with a total value of 1.